2017
DOI: 10.1108/mf-12-2015-0329
|View full text |Cite
|
Sign up to set email alerts
|

The influence of earnings management and bank structure on bank performance

Abstract: Purpose The purpose of this paper is to examine the influence of bank structure and earnings management on bank performance in international markets. Specifically, the authors empirically examine non-foreign banks in the following emerging countries: Brazil, China, India, Mexico, Nigeria, Russia, and South Africa. Design/methodology/approach A review of loan loss portfolio and bank’s power structure is examined to formulate testable conjectures. The authors used data collected from Bankscope for the aforemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Earnings management is an effort by management to intervene in preparing financial statements to achieve certain goals. Researchers measure the level of earnings management of Loan Loss Provisions (LLP) using the Kanagaretnam's Model, et al (2003) while the Loan Loss Allowance (LLA) by using the Hasan and Wall's ( 2004) model modified by Ujah (2017). Bonus is an independent variable in this study which will be measured using a dummy variable, where companies that distribute bonuses will be given a score of 1 and companies that do not distribute bonuses will be given a score of 0 (Pujiati and Muhammad, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Earnings management is an effort by management to intervene in preparing financial statements to achieve certain goals. Researchers measure the level of earnings management of Loan Loss Provisions (LLP) using the Kanagaretnam's Model, et al (2003) while the Loan Loss Allowance (LLA) by using the Hasan and Wall's ( 2004) model modified by Ujah (2017). Bonus is an independent variable in this study which will be measured using a dummy variable, where companies that distribute bonuses will be given a score of 1 and companies that do not distribute bonuses will be given a score of 0 (Pujiati and Muhammad, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Earnings management in the banking sector is achieved through the reduction of discretionary accruals from the total accrual. For this sector, earnings management is often reflected by Loan Loss Provision (LLP) (Othman & Mersni, 2014;Ujah et al, 2017). Banks use LLP to manage their earnings.…”
Section: Measurement Of Earnings Managementmentioning
confidence: 99%
“…A high activity level of earnings management can mislead financial statement users. The low quality of information generated from the adverse selection can affect a company's market value investor (Ujah et al, 2017). A company with a high level of integrity and credibility will acquire the public's trust (Mukherjee & Nuñez, 2019), and so raises its market value.…”
Section: Introductionmentioning
confidence: 99%
“…Business Standard has reported that Yes bank which is at the verge of bankruptcy has bad loans that are four times what Yes Bank had reported in its audited financial statements (Mukherjee, 2019, p. 4). EM results in poor financial performance of banks in long run Vision 25(2) (Alhadab & Al-Own, 2017;Ashfaq & Saeed, 2017;Ujah et al, 2017;Umoren et al, 2018;Wu et al, 2016). Thus, it becomes inevitable to detect EM at early stages.…”
Section: Introductionmentioning
confidence: 99%